2013
DOI: 10.1107/s2052519213013961
|View full text |Cite
|
Sign up to set email alerts
|

Influence of supramolecular structures in crystals on parallel stacking interactions between pyridine molecules

Abstract: Parallel stacking interactions between pyridines in crystal structures and the influence of hydrogen bonding and supramolecular structures in crystals on the geometries of interactions were studied by analyzing data from the Cambridge Structural Database (CSD). In the CSD 66 contacts of pyridines have a parallel orientation of molecules and most of these pyridines simultaneously form hydrogen bonds (44 contacts). The geometries of stacked pyridines observed in crystal structures were compared with the geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…This last conclusion was supported by later studies, which found that H-bonded pyridine rings have a clear preference for offsets of 1.25–1.75 Å. When the rings are not H-bonded, the offset is very variable and the separation between the ring planes increases. , …”
Section: Fundamental Sciencementioning
confidence: 67%
See 1 more Smart Citation
“…This last conclusion was supported by later studies, which found that H-bonded pyridine rings have a clear preference for offsets of 1.25–1.75 Å. When the rings are not H-bonded, the offset is very variable and the separation between the ring planes increases. , …”
Section: Fundamental Sciencementioning
confidence: 67%
“…When the rings are not H-bonded, the offset is very variable and the separation between the ring planes increases. 218,219 Geronimo et al found that positively charged nitrogen heterocycles (pyridinium and imidazolium) form offset, antiparallel stacking interactions much more often than edgeto-face contacts. The close proximity of the anionic counterions is very important in stabilizing the stacking arrangement.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Stacking interactions are central to many areas of chemistry, including the binding of ligands to proteins and nucleic acids, and harnessing such interactions lies at the heart of drug design. , In this context, understanding π-stacking interactions involving heterocycles is of paramount importance because heterocyclic fragments abound in drugs and bioactive natural products. Model π-stacking interactions involving heterocycles have been studied both experimentally and theoretically, , with the primary aim of unraveling the many factors that control their strength and preferred orientation. For instance, there have been numerous computational studies of non-covalent interactions involving pyridine as a model N-heterocycle, building on the seminal work on the benzene–pyridine and pyridine–pyridine dimers by Hohenstein and Sherrill .…”
Section: Introductionmentioning
confidence: 99%
“…Among different benzene core monocarboxylic acids, 3,5-dinitrobenzoic acid (3,5-Hdnb) represents a particularly interesting multifunctional ligand due to the presence of one carboxylic group capable of binding to metal ions in both anionic and neutral acid forms, two nitro groups for both complexation and noncovalent interactions and an aromatic ring favoring π-stacking interactions. In addition, an ancillary ligand like pyridine (py) is useful to prevent undesired aggregation of metal centers binding through its nitrogen atom as well as to provide supramolecular contacts. …”
Section: Introductionmentioning
confidence: 99%